Semantic loss in the holy Qur'an translation with special reference to surah al-WaqiAAa (chapter of the inevitable event) - Mohamed Abdelaal, Noureldin; Md Rashid, Sabariah (Sage Publications, 2015)
Semantic loss, which refers to over-, under-, or mistranslation of a source text (ST), may result in partial or complete loss of meaning in the target text (TT). This phenomenon is prevalent in the translations of an ST, especially translations of the Holy Qur’an due to factors such as the lack of equivalence of some cultural words in the target language (TL). In relation to this, translators of this holy book have been critiqued for their inability to completely convey the true and accurate meanings of the Holy Qur’an. This study attempted to investigate the semantic loss in the translation of the Surah al-WaqiAAa by Abdullah Yusuf Ali. It also examined the frequency and causes of such losses. This research, which is qualitative in nature, utilized descriptive content analysis of the Surah. The translation of the ayat [verses] related to the problem of the research has been extracted from the work of Abdullah Yusuf Ali, The Holy Qur’an: Text and Translation. The meanings of the translated verses were verified by two Arabic language experts who had mastered English as well. The causes of losses were identified according to Baker’s typology. The findings showed frequent partial and complete semantic loss of meanings mostly due to mistranslations, semantic complexity of the vocabularies, and culture.